The Impact of Manufacturing Digitization on Embodied Carbon Intensity: A Global Value Chain Perspective - Huang, Huiping; Zhou, Yihan; Shan, Yuanyuan (Transactions on Economics, Business and Management Research, 2023)
Climate issues have become one of the most important topics for the sustainable development of the global economy. Balancing trade gains with carbon emissions has become a strategic objective for each economy. Based on cross-country panel data from 2006-2018, this essay comprehends the relationship between manufacturing digitization and export embodied carbon intensity at the theoretical level and tests the theoretical arguments using panel models. In addition, the findings show that the digitization of manufacturing can reduce the export embodied carbon intensity through two paths: the deepening of the forward embeddedness and the improvement of the division of labor position in GVCs.